The Role of the CXCL12/CXCR4/CXCR7 Chemokine Axis in Cancer - Shi, Yi; Riese, David J.; Shen, Jianzhong (Frontiers in Pharmacology, 2020)
Chemokines are a family of small, secreted cytokines which regulate various cell functions. The C-X-C motif chemokine ligand 12 (CXCL12) binds to C-X-C chemokine receptor type 4 (CXCR4) and C-X-C chemokine receptor type 7 (CXCR7). The interaction of CXCL12 and its receptors subsequently induces downstream signaling pathways to affect chemotaxis, cell proliferation, migration, and gene expression. Accumulating evidence suggests that the CXCL12/CXCR4/CXCR7 axis plays a pivotal role in tumor development, survival, angiogenesis, metastasis, and tumor microenvironment. In addition, this chemokine axis promotes chemoresistance in cancer therapy via complex crosstalk with other pathways. Multiple small molecules targeting CXCR4/CXCR7 have been developed and used for preclinical and clinical cancer treatment. In this review, we describe the roles of the CXCL12/CXCR4/CXCR7 axis in cancer progression and summarize strategies to develop novel targeted cancer therapies.